Comparative analysis of Clostridium difficile clinical isolates belonging to different genetic lineages and time periods - Spigaglia, Patrizia; Mastrantonio, Paola (Journal of Medical Microbiology, 2004)
Recent studies have shown that Clostridium difficile strains with variant toxins and those with resistance to macrolide–lincosamide–streptogramin B (MLSB) are increasingly causing severe disease and outbreaks in hospital settings. Here, the pathogenicity locus (PaLoc), the acquisition of binary toxin, and the genotypic and phenotypic characteristics of antibiotic resistance of 74 C. difficile clinical strains isolated from symptomatic patients in Italy during different time periods were studied. These strains were found to belong to two different lineages, and those isolated before 1991 were genetically unrelated to the more recent strains. The majority of recent C. difficile strains showed variations in toxin genes and in the toxin negative regulator (tcdC) and had the binary toxin. In 62 % of them, variations in tcdC and the presence of the binary toxin were associated. Five classes of susceptibility/resistance pattern (EC-a to -e) for erythromycin and clindamycin were identified in all strains studied. Most of the recent isolates belonged to EC-d and EC-e and, although erythromycin-resistant in vitro, did not harbour the commonly associated ermB determinant. Interestingly, two strains of the EC-d class were resistant to clindamycin only after induction with subinhibitory concentrations of the antibiotic. A decrease in tetracycline and chloramphenicol MIC values was also observed in the recently isolated strains, associated with less frequent detection of the catD and tetM genes. Two tetM-positive strains were resistant in vitro only after induction with subinhibitory concentrations of the antibiotic. The acquisition of the binary toxin, the possible increase in toxin production due to a mutated negative regulator and a decrease in the fitness cost as a result of lower levels of antibiotic resistance or other mechanisms may have led to the successful establishment of these new phenotypes, with potentially serious clinical implications.